Concealed index for concealed penis in prepubertal children - Kobiljon Ergashev (Investigative and Clinical Urology, 2021)
Purpose: The concealed penis (CP) is a congenital or acquired genital anomaly that requires surgical correction. To construct an objective CP severity index, we compared the penile parameters of a CP with a normal penis (NP) and postoperative outcomes of CP patients. Materials and Methods: In this retrospective study, 391 boys under 14 years who visited our hospital between September 2017 and February 2020 were included. Among these boys, 105 patients had a CP and 286 boys had a NP without CP. The stretched penile length (SPL), penile circumference (PC), and penile length above baseline skin level (BPL) were measured using a ruler (cm), and the testicular volume was measured using an orchidometer (mL). We defined the concealed index according to SPL (CIs) as BPL/SPL and the concealed index according to circumference (CIc) as BPL/PC. A repair of the CP was performed in the CP patients. All parameters were measured before surgery and after three months. Results: The CP had significantly shorter SPL and BPL, and smaller CIs, and CIc than the NP. The cutoff values for the CIs and CIc were 0.68 and 0.58, respectively (sensitivity 86.7% and 86.7%; specificity 65.0% and 88.5%, respectively). After repair of the CP, all penile parameters were significantly improved. Conclusions: The CIs and CIc are useful and objective parameters for checking the severity of CP, and evaluating the postoperative outcome of CP repair. We newly introduced cutoff values for the CIs (0.68) and CIc (0.58) for diagnosing and evaluating CP repair.